Comparative analysis of performance between .NET platform versions - Grzegorz Grzegorczyk; Małgorzata Plechawska-Wójcik (Journal of Computer Sciences Institute)
The article analyzes the performance of traditional API controllers compared to MinimalAPI across various .NET platform versions, from 3.1 to 9 preview 3. The primary objective was to determine which technology offers superior performance in handling simple HTTP requests. For the analysis, a single application was developed in two variants: one using traditional API controllers and the other using MinimalAPI. This study provides significant insights into the efficiency of both approaches for handling HTTP requests on different .NET versions, contributing to a better understanding of their performance.